Cost-effectiveness of colorectal cancer screening under different scenarios of colonoscopy adherence: a microsimulation study - Juan Yang; Chen Yang; Wanghong Xu; Yongbing Xiang; Min Hu; Yuting Tan; Weimiao Wu; Kai Gu; Qiuming Shen (BMJ Public Health, 2025)
Introduction Low adherence to colonoscopy has greatly reduced the efficiency and cost-effectiveness of colorectal cancer (CRC) screening in China. This study aims to examine the cost-effectiveness of five initial tests followed by several scenarios of colonoscopy adherence.Methods A microsimulation model was constructed to compare the parallel use of risk assessment and two-specimen faecal immunochemical test (FIT) (currently used method in Shanghai) and several assumed initial tests (one-specimen FIT, two-specimen FIT, and risk scoring systems (RSS) incorporating one-specimen or two-specimen FIT) under adherence of observed levels, 50%, 60%, 70%, 80% or 90% among 100 000 individuals aged 50–74 years. Incremental cost-effectiveness ratios (ICERs) were computed using the currently used or the next most effective method as the reference. One-way and probabilistic sensitivity analyses were performed to assess the robustness of the findings.Results The RSS incorporating two-specimen FIT was more effective in reducing CRC incidence and mortality at colonoscopy adherence levels below 80%, whereas the currently used method performed better at higher adherence levels. The currently used method was effective and cost-effective for CRC screening, with an ICER relative to the next most effective method ranging from 153.000 to 29 165.120 CNY per quality-adjusted life-year. Enhancing adherence to colonoscopy increased the detection of early-stage CRC and improved the cost-effectiveness ratio and ICER of the current method. The current method had a probability of 35.5%, 34.5%, 35.5%, 40.0%, 32.0% and 38.0% for being the optimal strategy at observed level, 50%, 60%, 70%, 80% and 90% adherence, respectively, all within a willingness-to-pay threshold of 1 to 3 times the gross domestic product per capita.Conclusions The parallel use of risk assessment and two-specimen FIT is a cost-effective method for CRC screening in Chinese populations. Enhancing colonoscopy adherence may further improve the effectiveness and cost-effectiveness of the screening programme.